Karl Barth: Theologian of Christian Witness (Modern theology, 2006)
Book reviewed: Karl Barth: Theologian of Christian Witness by Joseph Mangina (Aldershot: Ashgate, 2004) xiv + 208 pp. Reviewed by Timothy J. Gorringe Department of Theology University of Exeter The Queen's Drive Devon EX4 4QJ UK